Internalisasi Nilai-Nilai Profetik Dalam Perkuliahan Program Studi Pendidikan Agama Islam Fakultas Tarbiyah IAIN Madura - Taqwim, Ibnan Ahsanut; Maghfiroh, Muliatul; Buna’i (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Education has an important role in shaping the character and spiritual values of students. The internalization of prophetic values is a fundamental aspect in Islamic Religious Education (PAI) at the Faculty of Tarbiyah IAIN Madura. Using a qualitative approach, this study observes and analyzes how prophetic values are implemented in the academic environment. This study uses a qualitative approach with a descriptive method. Data was collected through observation, interviews, and documentation. Data analysis techniques are carried out by condensation, data presentation, and verification and conclusion drawing. The results of this study show that the internalization of prophetic values in lectures in the PAI study program at the Faculty of Tarbiyah IAIN Madura is carried out by applying prophetic values such as (Siddiq) Lecturers apply honest behavior. (Trust) Be responsible for what has been entrusted by others. (tabligh) Conveying Islamic teachings in accordance with the Qur'an and Hadith. (Fathonah) Smart in making wise decisions. By teaching the science of monotheism in depth and approaching it in an Aqliyah and Naqliyah way. The strategy is carried out through: Moral Modelling, Habituation, Moral Knowing, Feeling and Loving the Good and Moral Action.